A method for repairing thick wall vertical through slit biomineralization layered printing

CN122707710APending Publication Date: 2026-09-08HUAQIAO UNIVERSITY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611197032.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-09-08

AI Technical Summary

Technical Problem

然而,目前MICP/EICP在裂缝修复方面的研究多针对尺度较小的裂缝,如混凝土板、砖块试件或薄层夯土试件中的微裂缝,裂缝宽度多在0.1 mm~1.5 mm范围内,修复对象均为实验室尺度试件或浅层表面裂缝

Benefits of technology

[0014] Compared with existing technologies, the biomineralized layered printing repair method for vertical through-cracks in thick walls provided by this invention firstly improves the strength and integrity of the wall material on the crack surface by pre-treating the vertical through-crack and pre-reinforcing the crack surface with biomineralization, thereby improving the interfacial compatibility and bonding performance between the subsequent filler and the original wall. Secondly, by dividing the vertical through-crack into several printing layers along the height direction, the deep and long crack space is discretized into multiple thin-layer units, realizing graded control of the geometric dimensions of the filler inside the crack, solving the problem of difficult precise positioning and uniform filling of the entire depth in the existing grouting process for deep and long cracks. Thirdly, by filling sand layer by layer from bottom to top and injecting biomineralization solution into each printing layer, the method achieves the following: This system enables the in-situ formation of calcium carbonate consolidation within the sand body, effectively controlling the spatial distribution of biomineralization products in each sand layer. This avoids the problems of uneven solution distribution and calcium carbonate precipitation at the bottom of the crack caused by gravity in one-time grouting in deep cracks. Finally, through a cyclical construction method of layer-by-layer sand filling and consolidation, a multi-layer composite filling structure composed of fine sand and calcium carbonate consolidation is constructed from bottom to top inside the vertical through crack. Under low-disturbance and low-pressure construction conditions, continuous and uniform filling and consolidation are achieved throughout the entire depth range of deep and long cracks. This ensures good compatibility between the repaired area and the original wall in terms of mechanical properties and physical characteristics, avoiding the risk of stress concentration and secondary cracking at the interface between the old and new surfaces caused by traditional rigid repair materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122707710A_ABST
    Figure CN122707710A_ABST
Patent Text Reader

Abstract

The present application relates to the field of civil engineering and cultural relic protection technology, and particularly relates to a kind of thick wall vertical through crack biomineralization layered printing repair method.The method comprises the following steps: pretreating the vertical through crack of thick wall, and spraying a biomineralization pre-reinforcement solution to the crack surface for pre-reinforcement; dividing the crack space into several printing layers along the height direction of the vertical through crack; performing sand filling and grouting steps layer by layer from bottom to top; for each printing layer, fill sand body into the crack space corresponding to the printing layer, and then inject a biomineralization solution system into the sand body to form calcium carbonate consolidation body inside the sand body; repeat the sand filling and grouting steps layer by layer until the construction of all printing layers is completed, and a multilayer composite filling structure composed of sand body and calcium carbonate consolidation body is formed inside the vertical through crack.The present application realizes the hierarchical control of the filling body inside the vertical through crack of thick wall, and is suitable for the vertical through crack repair of thick wall such as tulou and ancient city wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of civil engineering and cultural relic protection, specifically to a method for biomineralization layered printing repair of thick walls with vertical through-joints. Background Technology

[0002] Thick wall structures are widely found in traditional settlements and historical buildings, including the exterior walls of traditional rammed earth buildings such as Fujian Tulou and Hakka walled villages, as well as thick masonry walls such as ancient city walls, with wall thicknesses typically reaching 1.0 m to 2.0 m. Due to the combined effects of earthquakes, long-term deformation, and environmental erosion (rainwater soaking, wet-dry cycles, freeze-thaw cycles, etc.), these walls are prone to developing wide, through-cracks along their height, often exceeding 0.5 m in depth, and sometimes even penetrating the entire wall thickness. These cracks become the main channels for rainwater infiltration, localized damage, and overall instability. Existing crack repair methods mostly involve filling or grouting with cement mortar, lime mortar, polymer mortar, and chemical grouting materials. However, these rigid or semi-rigid materials differ significantly from rammed earth and brick in terms of elastic modulus, shrinkage performance, permeability, and thermal and moisture behavior. They are prone to stress concentration at the interface between old and new materials, and new microcracks are easily formed under subsequent changes in temperature, humidity, and load, leading to cracking of the repaired area again. High-performance chemical slurries can also significantly reduce the water vapor permeability of the cracked area, which has an adverse effect on the breathable enclosure structure of traditional buildings, and conflicts with the principles of minimal intervention and material compatibility in cultural relic protection.

[0003] Microbial-induced calcium carbonate (MICP) and enzyme-induced calcium carbonate (EICP) technologies have received widespread attention in geotechnical engineering and the preservation of historical buildings in recent years. These technologies induce calcium carbonate precipitation on the surface of sand, soil, or cracks by catalyzing the hydrolysis of urea with urease bacteria or free urease, in the presence of calcium ions. This significantly improves the mechanical properties of materials and reduces permeability. However, current research on MICP / EICP for crack repair mainly focuses on small-scale cracks, such as microcracks in concrete slabs, brick specimens, or thin-layer rammed earth specimens. The crack width is mostly in the range of 0.1 mm to 1.5 mm, and the repair targets are all laboratory-scale specimens or shallow surface cracks. For vertical through cracks in thick walls with a thickness of not less than 0.5 m and a crack depth greater than 0.5 m, existing research has not yet proposed a systematic biomineralization repair process, and there is a lack of effective technical means to achieve uniform filling and consolidation throughout the deep and long crack space. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for biomineralization layered printing repair of vertical through-joints in thick walls, comprising the following steps: S1: Pre-treat the vertical through joints of the thick wall, and spray the crack surface of the vertical through joint with a biomineralization pre-reinforcement solution for pre-reinforcement; S2: Divide the crack space into several printing layers along the height direction of the vertical through-slit; S3: The sand filling and grouting steps are performed layer by layer from bottom to top. For each printed layer, sand is filled into the crack space corresponding to the printed layer, and then a biomineralization solution system is injected into the sand to form a calcium carbonate solidified body inside the sand. S4: Repeat step S3 until all printing layers are completed, forming a multi-layer composite filling structure composed of sand and calcium carbonate solidified body inside the vertical through seam.

[0005] Furthermore, the wall thickness of the thick wall is not less than 0.5m, and the depth of the vertical through crack is greater than 0.5m; the thick wall includes rammed earth wall, brick and stone masonry wall, or a combination of the two.

[0006] Furthermore, in step S1, the pretreatment includes: cleaning loose particles and debris in and around the vertical through joint using an air jet method; sealing the open end of the vertical through joint with a sealing material compatible with the wall material, while retaining at least one construction side port.

[0007] Furthermore, in step S1, the biomineralization pre-consolidation solution is a microbial-induced calcium carbonate precipitation solution or an enzyme-induced calcium carbonate precipitation solution, wherein the concentrations of urea and calcium salt in the biomineralization pre-consolidation solution are each independently 0.2-1.0 mol / L, and the pH is 7.0-9.0.

[0008] Furthermore, in step S2, the thickness of each printed layer is 10-30 mm.

[0009] Furthermore, in step S3, sand is filled into the crack space corresponding to the printed layer using a low-pressure sand filling method, and vibration is applied to the filled sand to control the porosity of the printed layer sand within the range of 25%-40%.

[0010] Furthermore, in step S3, the biomineralization solution system includes a first solution and a second solution; the first solution contains urease bacteria or an enzyme source and contains urea, and the second solution contains calcium salt and urea; the concentration of urea in the first solution and the second solution is independently 0.2-1.0 mol / L, the concentration of calcium ions in the second solution is 0.2-1.0 mol / L, and the pH of the first solution and the second solution is independently 7.0-9.0.

[0011] Furthermore, in step S3, injecting the biomineralization solution system into the sand body includes: first injecting the first solution into the sand body, and then injecting the second solution into the sand body; the volume ratio of the first solution to the second solution injected in each round is 1:1-1:2.

[0012] Furthermore, in step S3, each of the printed layer sand bodies is injected at least twice, and the total volume of the first solution and the second solution injected in each round is 1.2-2.0 times the void volume of the printed layer sand body, and the time interval between adjacent rounds is 8-24 hours.

[0013] Furthermore, in step S3, sand and biomineralization solution system are filled into the crack space corresponding to the printed layer through a flexible pipe. The outer diameter of the flexible pipe is smaller than the width of the vertical through crack, and the length is greater than the depth of the vertical through crack. After at least the first round of grouting of the current printed layer is completed, the flexible pipe is left inside the sand of the printed layer for subsequent grouting and / or as a flexible reinforcement unit inside the filling body.

[0014] Compared with existing technologies, the biomineralized layered printing repair method for vertical through-cracks in thick walls provided by this invention firstly improves the strength and integrity of the wall material on the crack surface by pre-treating the vertical through-crack and pre-reinforcing the crack surface with biomineralization, thereby improving the interfacial compatibility and bonding performance between the subsequent filler and the original wall. Secondly, by dividing the vertical through-crack into several printing layers along the height direction, the deep and long crack space is discretized into multiple thin-layer units, realizing graded control of the geometric dimensions of the filler inside the crack, solving the problem of difficult precise positioning and uniform filling of the entire depth in the existing grouting process for deep and long cracks. Thirdly, by filling sand layer by layer from bottom to top and injecting biomineralization solution into each printing layer, the method achieves the following: This system enables the in-situ formation of calcium carbonate consolidation within the sand body, effectively controlling the spatial distribution of biomineralization products in each sand layer. This avoids the problems of uneven solution distribution and calcium carbonate precipitation at the bottom of the crack caused by gravity in one-time grouting in deep cracks. Finally, through a cyclical construction method of layer-by-layer sand filling and consolidation, a multi-layer composite filling structure composed of fine sand and calcium carbonate consolidation is constructed from bottom to top inside the vertical through crack. Under low-disturbance and low-pressure construction conditions, continuous and uniform filling and consolidation are achieved throughout the entire depth range of deep and long cracks. This ensures good compatibility between the repaired area and the original wall in terms of mechanical properties and physical characteristics, avoiding the risk of stress concentration and secondary cracking at the interface between the old and new surfaces caused by traditional rigid repair materials. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a schematic diagram of the process for the biomineralization layered printing repair method for vertical through-joints in thick walls according to the present invention; Figure 2 This is a schematic diagram of the object to be repaired according to the present invention; Figure 3 This is a cross-sectional schematic diagram of the layered sand filling method within the vertical through-slit of the present invention; Figure 4 This is the penetration path of the first solution within the vertical through-slit in the sand body according to the present invention; Figure 5 This is the penetration path of the second solution within the vertical through-slit in the sand body according to the present invention; Figure 6 This is a cross-sectional schematic diagram of the vertical through-joint filler and the surrounding thick wall after repair using the method of this invention.

[0017] Figure label: 1. Wall; 2. Outer side of the wall; 3. Inner side of the wall; 4. Top of the wall; 5. Bottom of the wall; 6. Upper interface of a single layer of sand; 7. Lower interface of a single layer of sand; 8. Sand particles filling the crack; 9. Sandblasting direction; 10. Sandblasting nozzle; 11. Vibrator; 12. Hoses; 13. Grouting port; 14. Interface; 15. First solution seepage direction; 16. Second solution seepage direction; 17. Calcium carbonate precipitation area. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] The specific implementation method of a biomineralization layered printing repair method for vertical through-cracks in thick walls is as follows: This embodiment uses the exterior wall of a circular traditional rammed earth building (a typical Tulou) as the object of repair. The wall 1 is 1.5m thick and 8.0m high. Within a section of the wall with a height of 3.0m, there is a vertical, wide, through-crack that runs through the outer side 2 and the inner side 3 of the wall. The crack is deeper than 0.5m, with an average width of about 15mm and a maximum width of about 25mm in some areas. It is a vertical through-crack in the thick wall.

[0020] Fine sand (less than 0.5mm) was selected as the crack filling material and dried in advance. The microbial system used Bacillus strains with high urease activity; bacterial suspensions were prepared with an OD concentration of [missing value]. 600 ≈1.0. The MICP reaction is carried out at room temperature (18~25℃) and pH (8.0~8.5) to complete the decomposition of urea and precipitation of calcium carbonate.

[0021] I. Pretreatment of vertical through joints and pre-reinforcement of crack surfaces with MICP First, clean the crack. Use an air gun with a pressure of about 0.4 MPa to blow along the vertical crack from the top 4 to the bottom 5 of the wall twice to remove loose particles and dust from the crack surface and the accessible area inside.

[0022] Then, end sealing is performed. A reversible sealing material compatible with rammed earth is used to seal the open ends of the vertical through joints on the outer side 2 and the inner side 3 of the wall, leaving only the outer side 2 of the wall as the working surface to prevent direct leakage of the subsequently injected solution.

[0023] Finally, pre-reinforcement with MIP spraying is performed on the crack surface. The pre-reinforcement solution is prepared with a bacterial concentration of OD... 600 The concentrations were approximately 1.0, urea 0.5 mol / L, calcium acetate 0.25 mol / L, and pH adjusted to approximately 8.5. A low-pressure spray gun was used to spray the solution onto the crack surface along the crack height, with a spray volume of approximately 1 L / m of crack height. After spraying, the solution was cured under environmental conditions for 48 hours. The strength of the rammed soil near the crack surface improved, and the apparent permeability decreased, providing a more stable interface for subsequent sand filling and grouting.

[0024] II. Layered Design and Backlash Sandblasting Filling Parameters The vertical through-slit at a height of 3.0m was divided into 150 printing layers with a layer thickness of 20mm. Under the conditions of an excitation frequency of about 50Hz and an amplitude of about 0.2mm, the 20mm thick fine sand layer can achieve good strength and uniformity after MICP treatment.

[0025] The flexible sandblasting hose 12 has an outer diameter of 8mm and a length of 1.8m. The front sandblasting nozzle 10 has a diameter of 6mm, and the vibrator 11 is installed 1030mm from the nozzle. The low-pressure sandblasting air supply pressure is controlled at approximately 0.15MPa, and the fine sand mass flow rate is approximately 0.5kg / min. Based on the average width of the vertical through-crack of 15mm and the wall thickness of 1.5m, the retraction speed of the sandblasting hose 12 can be set to approximately 0.5cm / s, ensuring that the sand layer thickness formed with each retraction is close to 20mm, meeting the design requirements for the printed layer thickness. The filling status of the crack is observed using a miniature camera.

[0026] III. First Printing Layer Fine Sand Laying The flexible sandblasting hose 12 is inserted from the top of the vertical through-slit on the outer side 2 of the wall until the sandblasting nozzle 10 is close to the closed position at the bottom 5 of the wall. Low-pressure sandblasting and vibrator 11 are started. The sand particles 8 filling the crack are sprayed out from the sandblasting nozzle 10 along the sandblasting direction 9. While supplying sand to the sand hopper, the hose is slowly lifted at a speed of about 0.5 cm / s to complete the laying of the first layer of fine sand. The upper interface of the sand body of the first layer is the upper interface 6 of a single layer of sand, and the lower interface is the lower interface 7 of a single layer of sand. By inserting a fine probe and a small endoscope, it is confirmed that the sand layer fills the width of the crack in the thickness direction, and the sand layer is relatively dense under the excitation of the vibrator 11 but still retains a certain amount of porosity. The porosity is measured to be about 35%.

[0027] IV. MICP Two-Step Grouting Parameters and Operation Regarding the solution preparation, the first solution is urease-containing bacterial solution plus urea solution: Bacillus concentration OD 600 The first solution is approximately 1.0, with a urea concentration of 0.5 mol / L and a pH of approximately 8.5. The second solution is a cementing solution: calcium acetate concentration 0.5 mol / L, urea concentration 0.5 mol / L, and pH of approximately 8.5.

[0028] Regarding the grouting channel, the flexible grouting hose 12 has an outer diameter of 6mm and a length of 1.8m. A radial grouting hole (approximately 1mm in diameter) is evenly distributed every 30mm within the corresponding printed layer height range. The hose's outer diameter is smaller than the crack width, allowing it to be inserted vertically through the crack to near the closed end of the inner wall 3. The grouting port 13 is located at the end of the hose on the outer wall 2 and is connected to the grouting pump via interface 14.

[0029] Regarding volume and number of cycles, based on an average vertical through-joint width of 15mm, a wall thickness of 1.5m, and a layer thickness of 20mm, the volume of sand in each printed layer is estimated to be approximately 450cm³. With a sand porosity of 35%, the void volume is approximately 158cm³. The total grouting volume for each cycle is 1.5 times the void volume, approximately 240mL. The volume ratio of the first solution to the second solution is approximately 1:1, with each solution approximately 120mL. Grouting is performed under low pressure, with the grouting pressure not exceeding 0.03MPa. The grouting flow rate per grouting hole is approximately 5~10mL / min, and the grouting time for one cycle per layer is approximately 60~80min. During grouting, the first solution permeates and distributes within the sand along the first solution seepage direction 15, followed by the second solution permeating and distributing within the sand along the second solution seepage direction 16. Upon encountering each other within the sand pores, a MICP reaction occurs, forming a calcium carbonate precipitation zone 17 around the sand particles.

[0030] Each printed layer of sand undergoes three rounds of two-step grouting, with an interval of approximately 12 hours between each round. This multi-round treatment ensures a relatively uniform distribution of calcium carbonate within the sand layer.

[0031] V. Layered Coordinated Construction and Grouting Channel Retention After completing the first two-step grouting of the first printed layer of sand, the second printed layer of fine sand is laid, and the retreating sandblasting and vibration compaction operations are repeated. A new flexible grouting hose 12 is inserted into the second printed layer of sand, and two-step grouting with the same mix ratio and volume is performed. All flexible grouting hoses 12 corresponding to each printed layer are left inside the sand body after the first round of grouting and consolidation of that layer, and are not removed. They are used to perform additional grouting on the middle and lower sand bodies after the upper layer construction is completed, and serve as flexible reinforcing elements along the vertical through-joint direction. The construction proceeds layer by layer from bottom to top. The upper interface 6 of the single layer of sand in the lower sand body is adjacent to the lower interface 7 of the single layer of sand in the upper sand body, and finally a multi-layer composite filling structure composed of sand particles 8 filling the cracks and calcium carbonate precipitation areas 17 is formed inside the vertical through-joint.

[0032] VI. Maintenance and Testing Results After the completion of all 150 layers of printed sand and the planned three rounds of grouting, the vertical through-joint areas of the exterior wall were cured for 28 days under natural conditions. During the first 7 days of curing, the crack areas were kept moderately moist by covering and spraying to promote the MIP reaction; thereafter, they were gradually allowed to air dry naturally.

[0033] Example 1 This embodiment uses the exterior wall of a circular traditional rammed earth building (a typical Tulou) as the object of repair. The exterior wall is approximately 1.5m thick and 8.0m high. Within a section of the wall, about 3.0m high, there is a wide, vertical crack that runs through both the inner and outer walls, which is a typical vertical crack in a thick wall. The average width of this vertical crack is about 15mm, with a maximum width of about 25mm in some areas, and it basically runs through the entire wall thickness along its height.

[0034] 1. Material parameters Fine sand (less than 0.5mm) was selected as the crack filling material and dried in advance. The microbial system used Bacillus strains with high urease activity; bacterial suspensions were prepared with an OD concentration of [missing value]. 600 ≈1.0. The MICP reaction is carried out at room temperature (18~25℃) and pH (8.0~8.5) to complete the decomposition of urea and precipitation of calcium carbonate.

[0035] 2. Vertical through-crack pretreatment and crack surface MIP pre-reinforcement (1) Crack cleaning: Use an air spray gun with a pressure of about 0.4 MPa to blow along the vertical through crack height from top to bottom twice to remove loose particles and dust from the crack surface and the accessible range inside; (2) End sealing: The open ends of the vertical through joints on the outer and inner sides of the outer wall are sealed with a reversible sealing material compatible with the rammed earth, leaving only the outer side as the construction operation surface to prevent the subsequent injected solution from leaking out directly; (3) Pre-reinforcement of crack surface by MICP spraying: Prepare a pre-reinforcement solution with a bacterial concentration of OD600≈1.0, a urea concentration of 0.5mol / L, a calcium acetate concentration of 0.25mol / L, and adjust the pH to approximately 8.5. Use a low-pressure spray gun to spray the solution onto the crack surface along the height of the crack, with a spraying amount of approximately 1L / m of crack height. After spraying, cure under environmental conditions for 48 hours. The strength of the rammed soil near the crack surface is improved, and the apparent permeability is reduced, providing a more stable interface for subsequent sand filling and grouting.

[0036] 3. Layered design and back-shock sand filling parameters The vertical through-slit at a height of 3.0m was divided into 150 printing layers with a layer thickness of 20mm. Under the conditions of an excitation frequency of about 50Hz and an amplitude of about 0.2mm, the 20mm thick fine sand layer can achieve good strength and uniformity after MICP treatment.

[0037] The flexible sandblasting hose has an outer diameter of 8mm, a length of 1.8m, and a front-end sandblasting nozzle diameter of 6mm. The vibrator is installed 30mm from the nozzle. The low-pressure sandblasting air supply pressure is controlled at approximately 0.15MPa, and the fine sand mass flow rate is approximately 0.5kg / min. The retraction speed of the sandblasting hose is set to approximately 0.5cm / s, ensuring that the sand layer thickness formed with each retraction is close to 20mm, meeting the design requirements for the printed layer thickness. The filling of the cracks is then observed using a miniature camera.

[0038] 4. Laying fine sand for the first printing layer Insert the flexible sandblasting hose from the top of the vertical through-gap on one side of the exterior wall until the sandblasting nozzle is almost closed at the bottom. Start low-pressure sandblasting and the front-end vibrator, and while supplying sand to the sand hopper, slowly lift the hose at a speed of about 0.5 cm / s to complete the laying of the first layer of fine sand. By inserting a fine probe and a small endoscopic device, such as a camera, it is confirmed that the sand layer fills the width of the crack in the thickness direction, and that the sand layer is relatively dense under the excitation but still retains a certain amount of porosity, with a measured porosity of about 35%.

[0039] 5. MICP Two-Step Grouting Parameters and Operation (1) Solution ratio: First solution (urease-containing bacterial solution with urea): Bacillus concentration OD600≈1.0, urea concentration 0.5mol / L, pH≈8.5; Second solution (cementing solution): calcium acetate concentration 0.5 mol / L, urea concentration 0.5 mol / L, pH≈8.5.

[0040] (2) Grouting channel: The flexible grouting hose has an outer diameter of 6mm and a length of 1.8m. A radial grouting hole (approximately 1mm in diameter) is evenly distributed every 30mm within the corresponding printed layer height range. The outer diameter of the hose is smaller than the crack width, and it can be inserted along the vertical through-crack direction to the vicinity of the closed end on the other side.

[0041] (3) Volume and number of rounds: Based on an average vertical joint width of 15mm, a wall thickness of 1.5m, and a layer thickness of 20mm, the volume of sand in each printed layer is estimated to be approximately 450cm³. With a sand porosity of 35%, the void volume is approximately 158cm³. The total grouting volume for each round of two steps is 1.5 times the void volume, approximately 240mL. The volume ratio of the first solution to the second solution is approximately 1:1, with each solution containing approximately 120mL. Grouting is performed under low pressure, with the grouting pressure not exceeding 0.03MPa. The grouting flow rate per grouting hole is approximately 5~10mL / min, and the grouting time for one round of a single layer is approximately 60~80min.

[0042] Each printed layer of sand undergoes three rounds of two-step grouting, with an interval of approximately 12 hours between each round. This multi-round treatment ensures a relatively uniform distribution of calcium carbonate within the sand layer.

[0043] 6. Layered collaborative construction and grouting channel placement After completing the first two-step grouting of the first printed layer of sand, the second printed layer of fine sand is laid, and the aforementioned retreating sandblasting and vibration compaction operations are repeated. A new flexible grouting hose is inserted into the second printed layer of sand, and two-step grouting with the same mix ratio and volume is performed. All flexible grouting hoses corresponding to each printed layer remain inside the sand body after the first round of grouting and consolidation of that layer, and are not removed. They are used for additional grouting of the middle and lower sand bodies after the upper layer construction is completed, and serve as flexible reinforcing elements along the vertical through-joint direction.

[0044] 7. Maintenance and Testing Results After the completion of all 150 layers of printed sand and the planned three rounds of grouting, the vertical through-joint areas of the exterior wall were cured for 28 days under natural conditions. During the first 7 days of curing, the crack areas were kept moderately moist by covering and spraying to promote the MIP reaction; thereafter, they were gradually allowed to air dry naturally.

[0045] After the maintenance is completed, local core samples are drilled and the repair effect is tested and evaluated.

[0046] Example 2 This embodiment focuses on a section of thick wall in the inner courtyard of a traditional rammed earth building, approximately 1.0m thick. Within a section of the wall, about 2.0m high, there exists a wide, vertical, continuous crack, characteristic of vertical continuous cracks in thick inner courtyard walls. This vertical crack has an average width of about 10mm, with a local width reaching 18mm, extending from the outer side to the middle of the wall, without completely penetrating the inner wall surface. To minimize the introduction of microorganisms and simplify the system, this embodiment employs the EICP method for biomineralization layered printing repair.

[0047] 1. Material parameters The filler aggregate is fine sand with a thickness of less than 0.25mm, which is dried in advance. The enzyme system uses crude urease extracted from 100g / L soybean flour solution, with an urease activity of approximately 20mM·min. - ¹. The EICP reaction was carried out at a temperature of 22–30 °C and a pH of 8.0–8.5.

[0048] 2. Pre-treatment of vertical wide joints and pre-reinforcement with EICP spraying (1) Crack cleaning: Use an air gun with an air pressure of about 0.3 MPa to clean the vertical through crack surface and the accessible area inside, removing loose particles and dust.

[0049] (2) End sealing: The outer end of the vertical through joint is sealed with a compatible sealing material, and an opening is reserved on the inner side for the insertion of pipes and observation.

[0050] (3) EICP spraying pre-reinforcement of crack surface: Prepare EICP spraying solution. Urease is derived from crude urease extracted from soybean flour solution. The concentration of soybean solution used is 100g / L, and the urease activity is about 20mM·min. - ¹, urea concentration 0.75mol / L, pH≈8.5; spray evenly along the vertical through crack height using a spraying method, with a spray volume of about 1L / m crack height, and keep the crack surface moist by covering and moderate spraying for the next 24 hours.

[0051] 3. Layered design and back-shock sand filling parameters The 2.0m vertical through-slit was divided into approximately 133 printing layers with a layer thickness of 15mm. Under the EICP system, the calcium carbonate precipitation was relatively uniform within the 15mm thick sand layer, while uneven consolidation occurred between the upper and lower parts due to excessively thick layers.

[0052] The flexible sandblasting hose has an outer diameter of 6mm, a length of 1.5m, and a front nozzle diameter of 4mm. The vibrator is installed 20mm from the nozzle. The low-pressure air supply is controlled at approximately 0.12MPa, and the fine sand mass flow rate is approximately 0.3kg / min. Based on an average vertical through-slit width of 10mm, an effective depth of 1.0m, and a target layer thickness of 15mm, the sandblasting hose retraction speed is approximately 0.6cm / s, and the excitation frequency is set to 60Hz to ensure the density and porosity distribution of each printed layer of sand. The filling status of the cracks is observed using a miniature camera.

[0053] 4. Parameters for each layer of sand laying and EICP two-step grouting Each printed layer of sand is laid using the same backward sandblasting method as in Example 1: the flexible sandblasting hose is inserted from the outer end of the through-slit to near the inner closed end, sandblasting and vibration are started, and the hose is slowly retracted at a speed of 0.6 cm / s to form a sand layer with a thickness of approximately 15 mm. The flexible grouting hose has an outer diameter of 4 mm, and a grouting hole is evenly distributed every 20 mm within the corresponding layer height range.

[0054] EICP solution is injected in two steps: The first solution is a urease-urea solution. The urease is crude urease extracted from soybean flour solution. The concentration of the soybean solution used is 100 g / L, and the urease activity is approximately 20 mM·min. - ¹, urea concentration 0.75 mol / L, pH≈8.5; The second solution is a calcium salt solution with a calcium acetate concentration of 0.75 mol / L and a pH of approximately 8.5.

[0055] Based on an average vertical joint width of 10mm, an effective depth of 1.0m, and a layer thickness of 15mm, the volume of a single layer of sand is estimated to be approximately 150cm³. With a sand porosity of 35%, the void volume is approximately 52.5cm³. The total grouting volume for each two-step grouting cycle is taken as 1.5 times the void volume, approximately 80mL, with approximately 40mL for each step. Grouting is controlled using a micro-pump, with the grouting pressure controlled to not exceed 0.02MPa. The flow rate per grouting hole is approximately 3~5mL / min to ensure slow distribution of the EICP solution within the sand, avoiding erosion of the precipitated calcium carbonate.

[0056] 5. Multiple rounds of treatment and grouting channel retention Under the above EICP mix ratio and sand layer parameters, a 15mm thick sand layer was subjected to three rounds of two-step grouting treatment, with a 12-hour interval between rounds.

[0057] The grouting hose corresponding to each sand layer is left inside the sand body after the first round of grouting and is not removed. After the upper sand body construction and initial consolidation are completed, additional EICP post-grouting can be performed on the middle and lower sand bodies through the left-in hoses to improve the overall calcium carbonate distribution. The left-in hoses act as flexible reinforcement in multi-layer sand bodies, helping to improve the integrity and tensile strength of the through-joint filler.

[0058] 6. Maintenance and Effect Evaluation After completing the sand layer construction and grouting, the area was cured for 21 days under on-site environmental conditions. During the first 7 days, the vertical through-joint area was kept moist by moderate water spraying and covering to meet the moisture requirements of the EICP reaction; thereafter, it was gradually allowed to air dry naturally.

[0059] Comparative Example To better illustrate the beneficial effects of the technical solution of the present invention, the following comparative examples are provided: Comparative Example 1: Single Grouting Repair The same type of vertical through-crack in a thick rammed earth exterior wall (wall thickness 1.5m, crack depth 3.0m, average width 15mm) as in Example 1 was used for repair. No layered treatment of the crack was performed; instead, fine sand was directly filled into the entire vertical through-crack in one go. Then, a MICP solution with the same proportions as in Example 1 (bacterial solution concentration OD) was injected in one go from the top of the crack or the construction side opening. 600 (Approximately 1.0, urea concentration 0.5 mol / L, calcium acetate concentration 0.5 mol / L, pH ≈ 8.5), the total grouting volume is calculated as 1.5 times the void volume of the sand body along the entire crack. Curing is performed for 28 days after grouting.

[0060] Comparative Example 2: Sand filling without layers but grouting in layers The same repair object as in Example 1 was used. No layered treatment of the crack was performed; instead, fine sand was filled into the entire vertical crack in one go (without layered filling and vibration compaction). Then, through multiple grouting points pre-embedded at different heights of the crack, MICP solution with the same proportions as in Example 1 was injected into different areas (upper, middle, and lower sections). The grouting volume for each section was calculated as 1.5 times the void volume of the sand in that section. Each section underwent three rounds of grouting, with a 12-hour interval between rounds. Curing was carried out for 28 days.

[0061] Comparative Example 3: Single-round grouting (no multi-round grouting) The same thick rammed earth exterior wall with vertical through-cracks as in Example 1 was used as the repair target. The repair was carried out in layers (20mm thick) and filled with sand layer by layer (porosity controlled at approximately 35%) according to the method of this invention. However, each printed layer of sand underwent only one round of two-step grouting (120mL of the first solution and 120mL of the second solution were injected), without multiple rounds of repeated grouting. Curing was carried out for 28 days.

[0062] Performance testing The vertical through-seam areas repaired using the examples and comparative examples will be sampled and tested using the following testing methods: (1) Shear strength: Core samples with a diameter of 50 mm and a height of 100 mm were drilled along the direction of the through joint in the repair area, and shear tests were conducted using a rock shear tester; (2) Compressive strength: A core sample with a diameter of 50 mm and a height of 100 mm was drilled from the repair area and a uniaxial compression test was conducted using a universal testing machine; (3) Permeability: Cube test blocks with a side length of 50 mm were cut from the repaired area, and the permeability coefficient was measured using a variable head permeameter. The average value of three test blocks was taken. Simultaneously, the permeability coefficient of the unrepaired rammed earth parent material was measured as a benchmark reference value (the permeability coefficient of the rammed earth parent material is approximately 1.2 × 10⁻⁶). -4 (cm / s).

[0063] The test results for each embodiment and comparative example are shown in Table 1.

[0064] Table 1

[0065] As shown in Table 1, after repair using MICP layered printing in Example 1, the shear strength of the repair reached 1.25 MPa, the compressive strength reached 3.82 MPa, and the permeability coefficient decreased to 6.3 × 10⁻⁶. -6 The flow rate was reduced by about two orders of magnitude compared to the unrepaired rammed earth parent material, indicating that calcium carbonate was evenly distributed within the sand layer, forming a dense, consolidated filling structure that effectively restored the mechanical properties of the cracked area and significantly reduced permeability.

[0066] Example 2 uses EICP layered printing for repair. Its shear strength and compressive strength are slightly lower than those of Example 1, but still much higher than all comparative examples. The permeability coefficient also meets the seepage prevention requirements, verifying the feasibility of the EICP system in the method of this invention.

[0067] In Comparative Example 1 (single-stage integral grouting), due to the lack of stratified treatment, the MIP solution was significantly affected by gravity in the deep and long cracks. Calcium carbonate precipitation concentrated at the bottom of the crack, and the top sand body was insufficiently consolidated, resulting in extremely low overall strength of the repair (compressive strength only 1.05 MPa) and a permeability coefficient reduced to only 4.7 × 10⁻⁶. -5 cm / s, resulting in poor seepage prevention.

[0068] Although Comparative Example 2 (sand filling without layering but grouting in layers) improved the uniformity of solution distribution, the sand filling in one go could not guarantee the consistency of sand porosity in the height direction, and the lack of layer-by-layer vibration densification resulted in uneven sand density. As a result, the strength and impermeability of the consolidated body were significantly worse than those of Example 1, indicating that the synergistic effect of layered sand filling and layered grouting is irreplaceable.

[0069] Comparative Example 3 (layered sand filling but only single-round grouting) had insufficient total calcium carbonate generated by the single-round MIP reaction, resulting in limited cementation between sand grains. Consequently, its compressive strength and shear strength were significantly lower than those of the multi-round treatment example. This indicates that multi-round grouting is crucial for ensuring sufficient and uniform consolidation within deep and long cracks.

[0070] Although this document frequently uses terms such as thick walls, vertical seams, printed layers, and biomineralization solutions, the possibility of using other terms is not excluded. These terms are used merely for the convenience of describing and explaining the essence of the invention; interpreting them as any additional limitation would contradict the spirit of the invention.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for repairing vertical through-joint biomineralization layered printing in thick walls, characterized in that: The steps include the following: S1: Pre-treat the vertical through joints of the thick wall, and spray the crack surface of the vertical through joint with a biomineralization pre-reinforcement solution for pre-reinforcement; S2: Divide the crack space into several printing layers along the height direction of the vertical through-slit; S3: The sand filling and grouting steps are performed layer by layer from bottom to top. For each printed layer, sand is filled into the crack space corresponding to the printed layer, and then a biomineralization solution system is injected into the sand to form a calcium carbonate solidified body inside the sand. S4: Repeat step S3 until all printing layers are completed, forming a multi-layer composite filling structure composed of sand and calcium carbonate solidified body inside the vertical through seam.

2. The method according to claim 1, characterized in that: The wall thickness of the thick wall is not less than 0.5m, and the depth of the vertical through crack is greater than 0.5m; the thick wall includes rammed earth wall, brick and stone masonry wall, or a combination of the two.

3. The method according to claim 1, characterized in that: In step S1, the pretreatment includes: cleaning loose particles and debris in and around the vertical through joint using an air jet method; sealing the open end of the vertical through joint with a sealing material compatible with the wall material, while retaining at least one construction side port.

4. The method according to claim 1, characterized in that: In step S1, the biomineralization pre-consolidation solution is a microbial-induced calcium carbonate precipitation solution or an enzyme-induced calcium carbonate precipitation solution, wherein the concentrations of urea and calcium salt in the biomineralization pre-consolidation solution are each independently 0.2-1.0 mol / L, and the pH is 7.0-9.

0.

5. The method according to claim 1, characterized in that: In step S2, the thickness of each printed layer is 10-30 mm.

6. The method according to claim 1, characterized in that: In step S3, sand is filled into the crack space corresponding to the printed layer using a low-pressure sand filling method, and vibration is applied to the filled sand to control the porosity of the printed layer sand within the range of 25%-40%.

7. The method according to claim 1, characterized in that: In step S3, the biomineralization solution system includes a first solution and a second solution; the first solution contains urease bacteria or an enzyme source and contains urea, and the second solution contains calcium salt and urea; The concentration of urea in the first solution and the second solution is independently 0.2-1.0 mol / L, the concentration of calcium ions in the second solution is 0.2-1.0 mol / L, and the pH of the first solution and the second solution is independently 7.0-9.

0.

8. The method according to claim 7, characterized in that: In step S3, injecting the biomineralization solution system into the sand body includes: first injecting the first solution into the sand body, and then injecting the second solution into the sand body; the volume ratio of the first solution to the second solution injected in each round is 1:1-1:

2.

9. The method according to claim 7, characterized in that: In step S3, each of the printed layer sand bodies is injected at least twice. The total volume of the first solution and the second solution injected in each round is 1.2-2.0 times the void volume of the printed layer sand body, and the time interval between adjacent rounds is 8-24 hours.

10. The method according to claim 1, characterized in that: In step S3, sand and biomineralization solution system are filled into the crack space corresponding to the printed layer through a flexible pipeline. The outer diameter of the flexible pipeline is smaller than the width of the vertical through crack, and the length is greater than the depth of the vertical through crack. After at least the first round of grouting of the current printed layer is completed, the flexible pipeline is left inside the sand of the printed layer for subsequent grouting and / or as a flexible reinforcement unit inside the filling body.